Numerical Methodologies for the Analysis of Horizontal-Axis Floating Offshore Wind Turbines (F-HAWTs): A State-of-the-Art Review - Naghmeh Akbari Zadeh; Peter Ryan; David M. Kennedy; Fergal O’Rourke (Energies)
In recent decades, wind turbine installations have become a popular option to meet the world’s growing demand for energy. Both onshore and offshore wind turbines form pivotal components of the electricity sector. Onshore wind energy is now a mature technology, with significant experience gained by wind farm developers and operators over the last couple of decades. However, as a more recent enterprise, the offshore wind industry still requires significantly more development before the technologies and operations reach maturity. To date, floating platforms at sea have been utilised extensively for the oil and gas industry. While a lot of the expertise and technology is transferable to the floating offshore wind industry, significant development work remains; for example, there is significant work required due to the different device types. Compared to floating oil and gas platforms, floating wind turbine platforms have a higher centre of gravity, which influences their performance and complexity. The successful large-scale development of floating offshore wind farms will require significant expertise and learning from the onshore wind, oil, and gas sectors. There are a wide range of software packages available to predict the operational behaviour of floating offshore wind turbines. In spite of this, it is still extremely difficult to create a fully coupled model of a floating wind turbine that can accurately and comprehensively model the turbine aerodynamics, hydrodynamics, servodynamics, structural dynamics, and mooring dynamics. This paper presents details on various fully coupled and uncoupled software packages and methodologies utilised to simulate floating offshore wind turbine performances. Various kinds of mooring systems, floating wind turbines, analysis methods, and experimental validation methods are comprehensively described. This paper serves as a reliable methodological guideline for researchers and wind industry professionals engaged in the design/analysis of wind farm projects.